Judgment and the Preparation of Educational Leaders. (September 2019) - Duke, Daniel L.
Should the topic of judgment have a place in the preparation and development of school leaders? This question serves as the focus for an examination of the nature of judgment and obstacles to good judgment. Judgment is defined as the ability to arrive at and make a choice when faced with incomplete information, uncertain conditions, and/or competing goals and values. The article argues that judgment and the related topics of decision making and problem solving are critical components of leader preparation. Suggestions are offered concerning judgment-related curriculum content and how it can be taught in pre-service and in-service settings.